2019
DOI: 10.3390/ijms20205145
|View full text |Cite
|
Sign up to set email alerts
|

A Cellularized Biphasic Implant Based on a Bioactive Silk Fibroin Promotes Integration and Tissue Organization during Osteochondral Defect Repair in a Porcine Model

Abstract: In cartilage tissue engineering, biphasic scaffolds (BSs) have been designed not only to influence the recapitulation of the osteochondral architecture but also to take advantage of the healing ability of bone, promoting the implant’s integration with the surrounding tissue and then bone restoration and cartilage regeneration. This study reports the development and characterization of a BS based on the assembly of a cartilage phase constituted by fibroin biofunctionalyzed with a bovine cartilage matrix, cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The fabrication of functionalized scaffolds with biological activity made of natural biomaterials is undoubtedly a promising approach ( Feng et al, 2020 ; Vainieri et al, 2020 ). Natural biomaterials such as dECM and natural polymers (collagen, silk fibroin, alginate, and chitosan) show repair potential in animal models of cartilage lesion ( Dai et al, 2019 ; Pérez-Silos et al, 2019 ; Singh et al, 2019 ). Tissue (or organ) from various species after decellularization can be utilized for the repair of a damaged tissue ( Sun et al, 2018 ; Lindberg et al, 2019 ).…”
Section: Immunological Characterization Of Biomaterialsmentioning
confidence: 99%
“…The fabrication of functionalized scaffolds with biological activity made of natural biomaterials is undoubtedly a promising approach ( Feng et al, 2020 ; Vainieri et al, 2020 ). Natural biomaterials such as dECM and natural polymers (collagen, silk fibroin, alginate, and chitosan) show repair potential in animal models of cartilage lesion ( Dai et al, 2019 ; Pérez-Silos et al, 2019 ; Singh et al, 2019 ). Tissue (or organ) from various species after decellularization can be utilized for the repair of a damaged tissue ( Sun et al, 2018 ; Lindberg et al, 2019 ).…”
Section: Immunological Characterization Of Biomaterialsmentioning
confidence: 99%
“…In the present study, the biphasic scaffolds developed had an upper 2-mm thick phase that simulates native cartilage conditions for further implantation, with native cartilage characteristics, such as flexibility, water retention and mechanical resistance to compression ( 25 ). The lower 4-mm thick phase of decellularized bone matrix chips served as support for the cartilage phase implantation and integration of cartilage with adjacent tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Full decellularization was assured by H&E staining. Bovine bone chips were obtained by perforation of the same bovine knees after cross-sectional slicing of the condyle area, followed by decellularization with hydrogen peroxide according to the decellularization method described by Pérez-Silos et al ( 25 ) to avoid host rejection of the material ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the animal studies with biphasic scaffolds, some studies set a control group in which is a single phasic scaffold was used [ [39] , [40] , [41] , [42] , [43] , [44] , [45] ]. Compared to the hyaline cartilage and porous bone regeneration with a clear tidemark observed in the group pf biphasic scaffolds, the inferior outcomes in the group of single chondral phase scaffolds included: subchondral bone formation and disordered fibrocartilage [ 39 ]; Disorganized fibrous tissue in both bone and chondral phase [ 40 ]; Lower ICRS II scores without regeneration of subchondral bone [ 41 ]; Slower cartilage and bone regeneration and integration with the native tissue [ 42 ]; A mixture of fibrocartilage and cartilage tissue [ 43 ]; Slower regeneration of bone layer [ 44 ]; fibrotic tissue separated from the surrounding bone [ 45 ]. In the studies of triphasic scaffolds, the corresponding control group of monophasic scaffolds also resulted in limited bone and cartilage repair with poor quality [ 34 , 46 ].…”
Section: Review Of Preclinical Studies On Osteochondral Tementioning
confidence: 99%
“…Many positive results have been reported using the combination of chondrocytes in the chondral layer and MSCs or osteoblasts in the bony layer for OCD repair, but several studies showed preloaded cells in the bone layer might lead to fibrocartilage formation due to excessive blood vessels formation. Perez-Silos group [ 40 ] found the scaffolds in which both osteoblasts and chondrocytes were loaded in the bone layer and chondral layer respectively (group 3) resulted in fibrocartilage repair. However, the group in which only chondrocytes were loaded on to the chondral layer (group 2) showed organized collagen II fibers and proteoglycans at the chondral layer and trabeculae in the bone layers.…”
Section: Review Of Preclinical Studies On Osteochondral Tementioning
confidence: 99%